ISOLATION, CHARACTERIZATION AND EFFECT OF AUXIN PRODUCING BACTERIA ON GROWTH OF TRITICUM AESTIVUM - K. Aziz; M. Nawaz; J. Nazir; A. A. Anjum; T. Yaqub; M.U.D. Ahmad; M. U. Rehman; G. Aziz; M. Khan (Journal of Animal and Plant Sciences, 2015)
Auxin, one of the most important phytohormones enhances the root architecture, nutrient acquisition and plant growth. Present study provides the screening, characterization and optimization of auxin producing bacteria from wheat rhizosphere. Effects of auxin producing isolates on seed germination and growth of T. aestivum were also evaluated. The Bacillus megaterium, Escherichia coli, Klebsiella pneumonia and Bacillus marinus (AUX36, AUX53, AUX137 and AUX142respectively) were selected by salkowski reagent as auxin producers. Colorimetric analysis showed that all selected isolates produced maximum auxin in the presence of tryptophan at 37 °C and pH 7 after 72 hours of incubation. AUX36 and AUX137 produced maximum auxin at 0.98% (w/v) NaCl concentration, while AUX53 and AUX142 at 2% NaCl. Glucose supplementation enhanced the auxin in the culture filtrate of AUX53 and AUX137, while addition of sucrose in the growth medium enhanced the auxin production for all isolates except AUX142. The AUX36, AUX53 and AUX137, produced highest concentration of auxin at 0.1% peptone. Seed germination experiments using surface sterilized seeds of T. aestivum revealed that all isolates could increase root length of seedlings as compared to control. Comparison of various growth parameters after 15 days of growth showed that plant growth was significantly improved by bacterial treatments. All isolates had significant effect on root and shoot length of T. aestivum. It is concluded that Bacillus megaterium AUX36, Escherichia coli AUX53, Klebsiella pneumonia AUX137 and Bacillus marinus AUX142may be used to develop indigenous biofertilizers in future after further investigations.
Keywords: Auxin; Phytohormones; Optimization; T. aestivum; B. megaterium